Fostering sustainable ventures: Drivers of sustainable start-up intentions among aspiring entrepreneurs in Pakistan. (20th July 2020) - Sher, Ali; Abbas, Azhar; Mazhar, Saman; Azadi, Hossein; Lin, Guanghua
Abstract: Promoting sustainable ventures among aspiring entrepreneurs could lead to an effective solution to reduce ecological footprints and help achieve the Sustainable Development Goals. Such an understanding has led to growing attention towards exploring entrepreneurship intentions across different entrepreneurial tiers and types, especially from the sustainability viewpoint. This study aimed at investigating the drivers of sustainable start-up intentions among university students which envision promoting the conservation of natural and ecological resources. This was accompanied by extending the theory of planned behavior to include attitude towards sustainable entrepreneurship and work values. The data set for present work consisted of responses obtained from 650 students pursuing university education in Punjab, Pakistan. The results reveal that attitude towards sustainable entrepreneurship, perceived entrepreneurial desirability and perceived entrepreneurial feasibility complement students' sustainability-driven entrepreneurial intentions. Environment value, extrinsic reward, intrinsic reward and general self-efficacy indirectly impact sustainability-driven entrepreneurial intentions. The study also reveals a contradictory role of job security inversely driving aspirations of sustainable entrepreneurship among budding entrepreneurs. Findings of the study highlight the importance of work values in the uptake of sustainability-driven entrepreneurship. This study provides insights for promoting sustainable opportunities and discusses the potential for sustainable entrepreneurship development. Moreover, findings also extend the existing literature on sustainable entrepreneurship, work values and uptake of sustainable ventures, and opportunities connected with sustainable ventures.